0279 Head and neck cancer and occupational exposure to chlorinated solvents: results from the ICARE study. (23rd June 2014) - Fayossé, Aurore; Menvielle, Gwenn; Cyr, Diane; Sanchez, Marie; Stucker, Isabelle; Luce, Danièle
Abstract : Objectives: To investigate the associations between head and neck cancer risk and occupational exposure to chlorinated solvents. Method: ICARE is a population based case-control study conducted in France. Analyses were restricted to men and included 1833 cases of head and neck squamous cell carcinomas (HNSCC) and 2747 controls. Complete occupational history was collected. Job-exposure matrices allowed to assess exposure to five chlorinated solvents (trichloroethylene, perchloroethylene, methylene chloride, chloroform and carbon tetrachloride). Odds ratios (ORs) adjusted for smoking, alcohol drinking and other potential confounders and 95% confidence intervals (CI) were estimated with logistic models. Results: No association was found for occupational exposure to trichloroethylene, methylene chloride, chloroform and carbon tetrachloride, and no dose-response relationships were observed. A non-significantly increased risk of HNSCC was observed for perchloroethylene (OR=2.1, CI 0.7–6.3), when comparing the highest tertile of cumulative exposure with no exposure. Analysis by cancer site showed that this increased risk was limited to laryngeal cancer. The risk of laryngeal cancer increased with cumulative exposure to perchloroethylene (p for trend=0, 03), with a significantly elevated OR (OR=5.0, CI 1.6–15.6) for the highest tertile of cumulative exposure. Exposure to perchloroethylene was not associated with the risk of oral or pharyngeal cancer. No associations were found between other chlorinated solvents and any of the cancer sites. Conclusions: These findings suggest that high levels of exposure to perchloroethylene may increase the risk of laryngeal cancer. Our study does not provide evidence that other chlorinated solvents are risk factors for HNSCC.